Triangulation and Gender Perspectives in ‘Falling Man’ by Don DeLillo (Altre Modernità, 2011)
Falling Man has often been read as the tale of of an American family trying to reinstate their ordinary lives after the 9/11 attacks, and their inability to do so due to the main protagonist’s entrapment in a traumatic state. I would argue instead that Falling Man adheres to a tradition of representations of masculinity distinguished by repressed grief and prolonged adolescence.Susannah Radstone argues that the rhetorical response to 9/11 by the Bush administration is based on the opposition of two father figures: “the 'chastened' but powerful 'good' patriarchal father” Vs. “the 'bad' archaic father”. She explains: “In this Manichean fantasy can be glimpsed the continuing battle between competing versions of masculinity” (2002:459) that leaves women on the margins. The battle of the fathers of Bush’s rhetoric is counterposed in Falling Man by a battle between two men that stands for an unaccomplished fatherhood. Furthermore, the dualistic vision engendered by post-9/11 rhetoric and reflected in the novel should be evaluated in a trilateral dimension, given that at its core lies a triangulation built upon three stereotypical representations: the white middle-class man; the Arab terrorist; and a composite character in the middle, the woman, who shifts from ally, to victim, to a plausible supporter of the enemy.
Keywords: Falling Man; Don DeLillo; Gender Perspective; 9/11 rhetoric; prolonged adolescence; triangulation.